2005
DOI: 10.6028/nist.ncstar.1-5
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the fires in the World Trade Center towers

Abstract: Certain commercial entities, equipment, products, or materials are identified in this document in order to describe a procedure or concept adequately or to trace the history of the procedures and practices used. Such identification is not intended to imply recommendation, endorsement, or implication that the entities, products, materials, or equipment are necessarily the best available for the purpose. Nor does such identification imply a finding of fault or negligence by the National Institute of .Standards a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…Although it may be possible to replicate these conditions in a furnace, a recent experimental review of post-flashover tests [15] has clearly demonstrated that temperature conditions are non-uniform in most compartments. Moreover, the major fires at the Windsor Tower [17], World Trade Center [18,19] and TU Delft [20] have shown that fires tend to travel around large compartments rather than burn uniformly. Tests have also shown the there is a high degree of temperature variation even within small compartments [21][22][23].…”
Section: Limitations Of Current Design Firesmentioning
confidence: 99%
“…Although it may be possible to replicate these conditions in a furnace, a recent experimental review of post-flashover tests [15] has clearly demonstrated that temperature conditions are non-uniform in most compartments. Moreover, the major fires at the Windsor Tower [17], World Trade Center [18,19] and TU Delft [20] have shown that fires tend to travel around large compartments rather than burn uniformly. Tests have also shown the there is a high degree of temperature variation even within small compartments [21][22][23].…”
Section: Limitations Of Current Design Firesmentioning
confidence: 99%
“…Due to the travelling nature of the fires, it is likely that temperature distributions during these events were highly non-uniform. While no data exist to validate this, extensive numerical simulations conducted for the World Trade Center investigations by NIST clearly show temperature variations within single compartments of several hundred degrees Celsius [18,19].…”
Section: Travelling Firesmentioning
confidence: 95%
“…Since the scale of most enclosures in real buildings is significantly larger than the scale in the few experimental tests available, it is likely that even higher degrees of non-uniformity are to be expected in real fires. Real, large fires that have led to structural failure, such as those in the World Trade Center towers 1, 2 [18] and 7 [19] in New York in September 2001, the Windsor Tower in Madrid, Spain in February 2005 [20] and the Faculty of Architecture at TU Delft in the Netherlands in May 2008 [21] were all observed to travel across floor plates. Due to the travelling nature of the fires, it is likely that temperature distributions during these events were highly non-uniform.…”
Section: Travelling Firesmentioning
confidence: 99%
“…Accidental fires that have led to structural failure [6,7,8,9] have been observed to travel across floor plates, and vertically between floors, rather than burn uniformly. Travelling fires have also been observed experimentally in compartments with non-uniform ventilation [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These two assumptions, which have never been confirmed experimentally, led to limitations in the use of the traditional methods in large compartments. Details of the limitations and their implications are given in Part I of this paper and in the literature [3,4,5].Accidental fires that have led to structural failure [6,7,8,9] have been observed to travel across floor plates, and vertically between floors, rather than burn uniformly. Travelling fires have also been observed experimentally in compartments with non-uniform ventilation [10,11,12].…”
mentioning
confidence: 99%